The Mini‐Organo: A rapid high‐throughput 3D coculture organotypic assay for oncology screening and drug development - Chitty, Jessica L.; Skhinas, Joanna N.; Filipe, Elysse C.; Wang, Shan; Cupello, Carmen Rodriguez; Grant, Rhiannon D.; Yam, Michelle; Papanicolaou, Michael; Major, Gretel; Zaratzian, Anaiis; Da Silva, Andrew M.; Tayao, Michael; et al. (Cancer reports, 2020)
Background The use of in vitro cell cultures is a powerful tool for obtaining key insights into the behaviour and response of cells to interventions in normal and disease situations. Unlike in vivo settings, in vitro experiments allow a fine‐tuned control of a range of microenvironmental elements independently within an isolated setting. The recent expansion in the use of three‐dimensional (3D) in vitro assays has created a number of representative tools to study cell behaviour in a more physiologically 3D relevant microenvironment. Complex 3D in vitro models that can recapitulate human tissue biology are essential for understanding the pathophysiology of disease. Aim The development of the 3D coculture collagen contraction and invasion assay, the “organotypic assay,” has been widely adopted as a powerful approach to bridge the gap between standard two‐dimensional tissue culture and in vivo mouse models. In the cancer setting, these assays can then be used to dissect how stromal cells, such as cancer‐associated fibroblasts (CAFs), drive extracellular matrix (ECM) remodelling to alter cancer cell behaviour and response to intervention. However, to date, many of the published organotypic protocols are low‐throughput, time‐consuming (up to several weeks), and work‐intensive with often limited scalability. Our aim was to develop a fast, high‐throughput, scalable 3D organotypic assay for use in oncology screening and drug development. Methods and results Here, we describe a modified 96‐well organotypic assay, the “Mini‐Organo,” which can be easily completed within 5 days. We demonstrate its application in a wide range of mouse and human cancer biology approaches including evaluation of stromal cell 3D ECM remodelling, 3D cancer cell invasion, and the assessment of efficacy of potential anticancer therapeutic targets. Furthermore, the organotypic assay described is highly amenable to customisation using different cell types under diverse experimental conditions. Conclusions The Mini‐Organo high‐throughput 3D organotypic assay allows the rapid screening of potential cancer therapeutics in human and mouse models in a time‐efficient manner.